Emerging Low‐Dimensional Materials for Nonlinear Optics and Ultrafast Photonics. Issue 14 (22nd February 2017) - Liu, Xiaofeng; Guo, Qiangbing; Qiu, Jianrong
Abstract : Low‐dimensional (LD) materials demonstrate intriguing optical properties, which lead to applications in diverse fields, such as photonics, biomedicine and energy. Due to modulation of electronic structure by the reduced structural dimensionality, LD versions of metal, semiconductor and topological insulators (TIs) at the same time bear distinct nonlinear optical (NLO) properties as compared with their bulk counterparts. Their interaction with short pulse laser excitation exhibits a strong nonlinear character manifested by NLO absorption, giving rise to optical limiting or saturated absorption associated with excited state absorption and Pauli blocking in different materials. In particular, the saturable absorption of these emerging LD materials including two‐dimensional semiconductors as well as colloidal TI nanoparticles has recently been utilized for Q‐switching and mode‐locking ultra‐short pulse generation across the visible, near infrared and middle infrared wavelength regions. Beside the large operation bandwidth, these ultrafast photonics applications are especially benefit from the high recovery rate as well as the facile processibility of these LD materials. The prominent NLO response of these LD materials have also provided new avenues for the development of novel NLO and photonics devices for all‐optical control as well as optical circuits beyond ultrafast lasers. Abstract : Two‐dimensional materials, topological insulators, and plasmonic nanomaterials exhibit distinct and intriguing electrical and optical properties, making them the focus of intensive research in the past decade. Their interactions with intense pulse lasers are strongly nonlinear, and, surprisingly, all of them can serve as efficient saturable absorbers to enable ultrafast pulse generation in a wide spectral range.